Biomechanical optimization of the magnesium alloy bionic cannulated screw for stabilizing femoral neck fractures: a finite element analysis - Cui, Yunwei; Ding, Kai; Lv, Hongzhi; Cheng, Xiaodong; Fan, Zixi; Sun, Dacheng; Zhang, Yifan; Chen, Wei; Zhang, Yingze (Frontiers in Bioengineering and Biotechnology, 2024)
The magnesium alloy bionic cannulated screw (MABCS) was designed in previous study promoting cortical-cancellous biphasic healing of femoral neck fracture. The main purpose was to analyze the bore diameters that satisfy the torsion standards and further analyze the optimal pore and implantation direction for stabilizing femoral neck fractures. Methods: The MABCS design with bionic hole less than 20% screw diameter met the torsion standard for metal screw. MABCS were utilized to repair the femoral neck fracture via Abaqus6.14 software, which simulated the various stages of fracture healing to identify the optimal biomechanical environment for bionic hole size(5%, 10%, 15% and 20%) and implantation direction(0°, 45°, 90°and 135°). Results: The stress distribution of MABCS fracture fixation model is significantly improved with an implantation orientation of 90°. The MABCS with 10% screw diameter bionic hole provides the optimal stress distribution compared with the 5%, 15%, and 20% diameter bionic cannulated screw. According to the fracture fixation analysis, the 10% bionic hole size cannulated screw fixation model has the optimal stress distribution of bone and internal fixation than 5%, 15% and 20% screw diameter MABCS fixation models.In summary, the MABCS with 10% screw diameter bionic hole has exhibits favorable biomechanical characteristics for stabilizing femoral neck fractures. This study provides a biomechanical foundation for further optimization of the bionic cannulated screw.